2016
DOI: 10.4103/2278-0203.176652
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial properties of poly (methyl methacrylate) acrylic resins incorporated with silicon dioxide and titanium dioxide nanoparticles on cariogenic bacteria

Abstract: Aim:To assess the effects of adding nano-titanium dioxide (nano-TiO2) and nano-silicon dioxide (nano-SiO2) and their mixture to poly (methyl methacrylate) (PMMA) to induce antimicrobial activity in acrylic resins.Materials and Methods:Acrylic specimens in size of 20 mm × 20 mm × 1 mm of 0.5% and 1% of nano-TiO2 (21 nm) and nano-SiO2 (20 nm) and their mixture (TiO2/SiO2 nanoparticles) (1:1 w/w) were prepared from the mixture of acrylic liquid containing nanoparticles and acrylic powder. To obtain 0.5% and 1% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 33 publications
1
12
0
1
Order By: Relevance
“…It was in line with Totu et al's study [ 32 ], which found that incorporating even small amounts of 0.4% TiO 2 nanoparticles to a 3D-printed PMMA denture prevented the colonization of microorganisms and further biofilm formation. Another study showed that adding TiO 2 and SiO 2 nanoparticles (0.5% and 1%) to PMMA imparted antimicrobial activity to the resins, being even more efficient under UVA exposure [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was in line with Totu et al's study [ 32 ], which found that incorporating even small amounts of 0.4% TiO 2 nanoparticles to a 3D-printed PMMA denture prevented the colonization of microorganisms and further biofilm formation. Another study showed that adding TiO 2 and SiO 2 nanoparticles (0.5% and 1%) to PMMA imparted antimicrobial activity to the resins, being even more efficient under UVA exposure [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its photocatalytic ability promoted it to be known as an antimicrobial agent encouraging its addition to biomaterials [11, 12, 20, 23, 25]. TiO 2 NP have been found effective against a wide range of microorganisms including gram-positive and gram-negative bacteria, fungi, and viruses [11, 23, 25].…”
Section: Introductionmentioning
confidence: 99%
“…An important direction of the research related to the use of PMMA-based materials is their modification aimed to improving their antimicrobial activity. This effect can be achieved by the addition of inorganic agents such as silver nanoparticles, titanium dioxide, a mixture of titanium dioxide and silicon dioxide nanoparticles, and anion powder (Na 2 SiO 3 ) [ 29 , 30 , 31 , 32 , 33 , 34 ]. In this paper, the results of the modification of the PMMA films by the introduction of TOC micro-grains are discussed.…”
Section: Introductionmentioning
confidence: 99%